1999
DOI: 10.1002/(sici)1097-4598(199909)22:9<1265::aid-mus15>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maximal voluntary isometric contraction and Drachman's hand-held dynamometry in evaluating patients with amyotrophic lateral sclerosis

Abstract: Maximal voluntary isometric contraction (MVIC) is a standard tool for assessment of muscle strength in treatment trials for amyotrophic lateral sclerosis (ALS). There is need for more practical bedside techniques especially for severely disabled patients. Hand‐held dynamometry (HH‐Dyn) is an inexpensive and easy‐to‐handle device. MVIC was measured in five proximal muscle groups bilaterally and compared with HH‐Dyn in 43 ALS patients. After a training period we found good intrarater correlation for HH‐Dyn (r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 20 publications
3
37
0
3
Order By: Relevance
“…The degree and progression of weakness in IBM and PM-Mito patients was evaluated during the clinical examinations by measuring quantitative levels of strength in two muscle groups that are commonly involved in IBM, ventral muscles of the forearm (grip) and knee extension. Quantitative strength testing was performed by a validated method of hand-held dynamometry [16,17]. Each measurement was converted to a percent of normal strength to permit averaging of muscles.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The degree and progression of weakness in IBM and PM-Mito patients was evaluated during the clinical examinations by measuring quantitative levels of strength in two muscle groups that are commonly involved in IBM, ventral muscles of the forearm (grip) and knee extension. Quantitative strength testing was performed by a validated method of hand-held dynamometry [16,17]. Each measurement was converted to a percent of normal strength to permit averaging of muscles.…”
Section: Methodsmentioning
confidence: 94%
“…Myopathologic characteristics included an inflammatory myopathy (myopathic changes and foci of endomysial or perimysial mononuclear cell inflammation), but no vacuoles or mitochondrial abnormalities. Clinically, there was improvement in strength (clear functional improvement by history, and improvement of the average quantitative strength in 6 proximal muscles by at least 20% of normal levels [17]) after corticosteroid treatment. Clinical records showed that all IBM, PM-Mito and polymyositis patients had muscle weakness on physical examination and an abnormal EMG with myopathic motor units and spontaneous activity.…”
Section: Methodsmentioning
confidence: 99%
“…Since, maximum grip strength is a common clinical measure we used a second force level of 70% MVC to better align our paradigm with existing clinical measures without introducing the risk of fatigue. A change in maximum grip strength, from a higher to lower value is indicative of the progressive decline in muscle strength that differs as a function of age and/or the onset of musculoskeletal and neurological impairments (Beck et al, 1999; Visser et al, 2003). The rate of change in the decline of hand grip strength is different for the right and left hand (Chatterjee and Chowdhuri, 1991), will be more evident at higher than lower force levels, and differs for men and women (Vianna et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This includes the force of the handgrip in the clinical setting [6] and the contraction force of muscle groups under laboratory conditions [7-13]. Maximum voluntary contractions are difficult to define in relation to the muscles involved, and are subject to increased variability compared to electrically stimulated contractions.…”
Section: Introductionmentioning
confidence: 99%